Hubungan antara reseptor progesteron dengan Ki-67 labeling index pada meningioma - Steven Tandean; Rr Suzy Indharty; Iskandar Japardi; Sufida dr (Fakultas Kedokteran USU, 2013)
Introduction : Meningiomas are benign tumor and the most prevalent intracranial tumors which recur locally. Their morphologic grading do not always correlate with patient outcome and some of them associated with a less favorable clinical outcome. The incidence in women is approximately twice than in men. Progesterone receptors may play role in the proliferation and grading of meningiomas. Aims of this study isto evaluate the correlation of progesterone receptor status with proliferation marker ki67 in various grades of meningioma.Methods : A retrospective research of 30 paraffin-embedded sections of meningiomas was collected that was done histological typing and grading with hematoxylin and eosin. Immunodetection of Progesterone receptors was conducted with peroxidaseantiperoxidase complex and Ki-67 was achieved by streptavidin-biotin peroxidase complex. Progesterone receptors status considered positive if >50% of nuclei were stained with medium intensity or >10 of tumor cell’s nuclei were strongly stained. The Ki-67 is defined into three groups as no proliferation, low proliferation (<14%), and high proliferation (> 14%). Results : Progesterone receptors were positive in 13/27 (48.1%) of grade I tumors, 1/2 (50%) of grade II tumors, and 0/1 (0%) of grade III tumor. In grade I tumor, negative progesterone receptors with negative Ki-67 was 6/14 (42.9%) and low Ki-67 was 8/16 (57.1%). While, positive progesterone receptors with negative Ki-67 was 7/13 (53.8%), low Ki-67 was 4/13 (30.8%), and high Ki-67 was 2/13 (15.4%). In grade II tumor, negative progesterone receptors with negative Ki-67 and positive progesterone receptors with low Ki-67 expression. In grade III tumor, negative progesterone receptors with negative Ki-67 expression. Conclusion : There was a not significant relationship between Ki-67 and progesterone receptors status, but high Ki-67 expression was only found in positive progesterone receptors. Progesterone receptors may play role in proliferation of meningioma. Keywords : meningioma; progesterone; receptor; Ki-67 antige